Eficiência alimentar e parâmetros produtivos em bezerras F1 Holandês x Gir - Juliana Mergh Leao (2018)
The aims of this study were to assess if there is phenotypical divergence for feed efficiency (FE) during the preweaning phase, if FE is correlated with heat production (HP) measured by the face mask method or by surface skin temperature via thermography, and whether these methods are applicable to preweaned calves it was also evaluated feed efficiency indexes and its effects on body measurements, blood and ruminal metabolites. Holstein x Gyr heifer calves (n = 36, birth BW = 32.4 ± 6.6 kg) enrolled between 4th and 12th w of age were classified into two residual feed intake (RFI) and residual growth (RG) groups: high efficiency (HE; RFI, n = 10; and RG, n = 9), and low efficiency (LE; RFI , n = 10; and RG, n = 8). Calves were fed milk (6 L/d) and solid feed (95% starter and 5% chopped Tifton 85 hay, as-fed). Growth were monitored weekly and feed intake (milk and solid feed) daily, during the whole period. Gas exchanges (O2 consumption and production of CO2 and CH4) were obtained using a face mask at 45 ± 5 d of age and HP was estimated. Maximum temperatures were measured at 7 sites with an infrared camera at 62 ± 7 d of age. Blood samples were collected on 12th w and analyzed for glucose, insulin and BHBA. Rumen samples collected on the same day and analyzed for pH, Total volatile fatty acids (VFA), acetic, butyric, and propionic. A completely randomized design was used, data were analyzed using ANOVA and correlations. Means were compared using Fishers test. There was divergence in RFI and RG. Respectively, HE and LE calves had RFI of -0.14 kg/d and 0.13 kg/d, and RG of 0.05 kg/d and -0.07 kg/d. Dry matter intake (DMI) was 15% lower in HE-RFI compared with LE-RFI, but there were no differences in average daily weight gain (ADG). Within the RG test, there were no differences in DMI or ADG. HE-RFI calves consumed less O2 (L/d) and produced less CO2 (L/d). Heart rate and HP were lower for HE-RFI calves compared with LE-RFI. RFI was correlated with HP (r = 0.48), O2 consumption (r = 0.48), CO2 production (r = 0.48), and heart rate (r = 0.40). There were no differences in HP and gas exchanges between RG groups. Methane production was null in both groups. Eye temperature measured by thermography was 0.5°C greater in HE-RG than LE-RG calves. Differences in skin temperature between HE and LE calves were not observed at the other sites. There were no significant differences between the RFI and RG classes for ruminal pH, ruminal NH3N concentration, proportion of VFA and molar proportions of propionic and acetic acids. For butyric acid no differences were found between RFI groups but tended to be higher in HE residual gain groups. No differences in glucose, insulin and insulin to glucose between the groups were found. For â-hydroxybutyrate (BHBA) and glucose to insulin no differences exist in RFI groups but tended to be higher in HE residual gain animals. There were also no significant differences between the RFI classes for growth characteristics, except for inicial hip width for RFI group and variation of withers high for RG group (P< 0.05). These results support the hypothesis that calves are divergent for RFI, RG and FE during preweaning and divergence tests are applicable during this phase. The face mask method described here is a useful tool for estimating differences in HP among phenotypically divergent RFI calves. Eye temperature measured by IRT may have potential to screen phenotypically divergent RG calves. Overall, the correlation coefficient estimates between the potential blood markers and measurements of rumen and morphometric traits were weak and generally not different from zero. This suggests that it is unlikely that measurement of these metabolic indicators, per se, will be useful in the early identification of feed efficient animals during preweaning phase.